Pendampingan Penguatan Karakter Keislaman pada Generasi Usia Dini sebagai Upaya Mewujudkan Indonesia Emas 2045 - Khoirun Nasik; Tri Pujiati (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
Character education strengthening is an urgent necessity in preparing for Indonesia’s Golden Generation 2045. Early Childhood Education (ECE) plays a strategic role as the foundational stage for character formation. This community service program aims to develop an Islamic character-building model based on synergy between teachers and parents in ECE institutions across Dukun District. The program applies an integrated approach consisting of training, habituation, actualization, and continuous monitoring. The methods employed include paradigm-based training on character education, value habituation in both school and home environments, practical implementation in daily life, and sustained mentoring. The findings reveal a significant increase in collective awareness among teachers and parents regarding shared responsibility in character education. Furthermore, value alignment between school and home environments was successfully established, leading to more consistent and stable character internalization in children. Parental participation also increased substantially, shifting from passive involvement to active partnership in shaping children’s character development. The staged process from understanding to habituation proved effective in strengthening value internalization into children’s daily behavior. Moreover, the model demonstrates strong sustainability potential through the involvement of HIMPAUDI, enabling broader replication across ECE institutions. Overall, the model effectively contributes to the development of a collaborative, systematic, and sustainable character education ecosystem at the early childhood level. This program also contributes to the achievement of the Sustainable Development Goals, particularly SDG 4 (Quality Education), by promoting inclusive, equitable, and quality education through strengthened character education and school–family collaboration, as well as SDG 17 (Partnerships for the Goals) through reinforced multi-stakeholder cooperation among teachers, parents, and professional organizations in advancing sustainable education.